2009
DOI: 10.3899/jrheum.081320
|View full text |Cite
|
Sign up to set email alerts
|

Can Magnetic Resonance Imaging Differentiate Undifferentiated Arthritis Based on Knee Imaging?

Abstract: Patients with RA showed more destructive changes in terms of synovial thickening, bone marrow edema, cartilaginous and bone erosions compared to UA and SpA groups. Enthesitis is a common feature on MRI in SpA, while absent in the RA and UA groups. This latter finding may have important clinical implications for classification purposes, and can help to determine the evolving pattern of patients with UA of the knee joint.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 29 publications
2
16
0
Order By: Relevance
“…This finding was confirmed by our group 5 . We compared enhanced MRI findings of the knee joints in 3 groups of patients, undifferentiated arthritis (UA; n = 25), established RA (n = 15), and SpA (n = 15), and found that enthesitis was a common feature on MRI in the SpA group, was totally absent in the group of patients with RA, and was observed in 3 patients in the UA group.…”
supporting
confidence: 81%
See 2 more Smart Citations
“…This finding was confirmed by our group 5 . We compared enhanced MRI findings of the knee joints in 3 groups of patients, undifferentiated arthritis (UA; n = 25), established RA (n = 15), and SpA (n = 15), and found that enthesitis was a common feature on MRI in the SpA group, was totally absent in the group of patients with RA, and was observed in 3 patients in the UA group.…”
supporting
confidence: 81%
“…Bone was assessed for marrow signal intensity abnormalities and focal erosions. Maximal synovium thickness was measured in the suprapatellar pouch on sagittal T1-weighted Gd-enhanced images, as in our earlier studies 4,5 . Special emphasis was given to the following entheseal sites and they were carefully evaluated for abnormalities: the quadriceps tendon insertion and the proximal and distal patellar tendon.…”
Section: Severitymentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the absence of psoriatic skin lesions does not always exclude the diagnosis of PsA, especially in the absence of other important features of the disease (e.g., finger nail dystrophy, seronegativity for RF, distal interphalangeal joint involvement, oligoarthritis, asymmetry, and dactylitis) [10].…”
Section: Discussionmentioning
confidence: 99%
“…Interpretation of these data is complicated by the fact that these studies used different approaches (MRI, ultrasound, Power Doppler ultrasound) and enthesitis scores. This results in wide variability of findings with, for example, a reported frequency of enthesitis ranging from no enthesitis at all6 8 to 60% in RA 4. To avoid potential biases, we based our approach on the study by McGonagle et al ,2 focusing on the same patient groups and using globally the same MRI parameters.…”
Section: Discussionmentioning
confidence: 99%